Elegy - Levis, Larry (University of Pittsburgh Press, 1997)
A few days before his death in 1996, Larry Levis mentioned to his friend and former instructor Philip Levine that he had "an all-but-completed manuscript" of poems
Keywords: American poetry -- 20th century.; Poésie américaine -- 20e siècle.; LITERARY CRITICISM -- Poetry.; POETRY -- American -- General.; American poetry; 1900-1999; Poetry (Poetic Works By One Author); Poetry